The Impact of Ribbon Properties on Measured Peel Forces. (August 2016) - Eitner, Ulrich; Rendler, Li C.
Abstract: The peel test of soldered/glued ribbons on solar cell metallizations is the critical test in the PV industry and research community to qualify the integrability of cells into modules. It has been shown that the peeling angle of the test setup strongly influences the measured peel forces [1, 2], leading to higher forces for decreasing peeling angles < 90̊ and weakest forces for 135̊. Here, we apply the theory of Kinloch and Kawashita [3, 4] to determine the adhesive fracture energies G A from 180̊ peel tests of three different ribbons which differ in compliance (softness) and thickness. The experiments show that the soft ribbon ( σ y = 62MPa) gives lower peel forces than the stiff ribbons ( σ y = 99MPa) while the adhesive fracture energies are higher. The thickness variation from 150 μm to 200 μm of the hard ribbon has no significant effect on the adhesive energy. Furthermore, our investigation confirms that switching from 90̊ peeling angles to 180̊ helps to reduce silicon fracture patterns at high forces. In conclusion, the adhesion does not only depend on the surface properties of cell metallization schemes and soldering conditions, but also on the choice of ribbon used for the peel test. We therefore recommend to use the adhesive fracture energy G A instead of the normalized peel forces to improve the consistency and comparability between different peel testing setups and ribbon materials as the peel test is essential for accepting (or rejecting) novel metallization concepts (plating, metallization pastes) and interconnection technologies (low melting solder alloys, conductive adhesives).